Proximate, fatty acid and mineral composition of hilsa, Tenualosa ilisha (Hamilton 1822) from the Bay of Bengal and Arabian Gulf - Hossain, M. A.; Almatar, S. M.; Al-Hazza, A. A. (Indian Journal of Fisheries, 2014)
Fish is the best source of n-3 polyunsaturated fatty acids (PUFAs), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The objective of this study was to investigate the proximate, fatty acid and mineral composition of hilsa (Tenualosa ilisha) from the Bay of Bengal and Arabian Gulf. In general, egg protein and lipid contents were significantly (p<0.05) higher than those of the muscle tissues. However, lipid contents of muscle and egg tissues of hilsa from the Bay of Bengal were significantly (p<0.05) higher than those of the Arabian Gulf. Iron, zinc and manganese content in eggs were significantly higher than those of muscle tissues, while calcium and potassium in muscle were significantly higher in egg tissues (p<0.05). Among the saturated fatty acids (SFA) and monosaturated fatty acids (MUFA) in both tissues, palmitic acid (C16:0) and oleic acid (C18:1n-9) were the principal SFA and MUFA, respectively. There was no significant difference between the Î£PUFAs of both muscle and egg tissues and the PUFAs were dominated by both EPA and DHA. Among the Î£PUFAs, Î£n-3 PUFAs constituted about 80%. The result of the study showed that both hilsa muscle and egg represent a very good source of n-3 PUFA for human diet. However, hilsa from the Bay of Bengal could be a better source of n-3 PUFA, because of higher lipid content in its muscle compared to that of the Arabian Gulf.